Myotrioza myopori Taylor, a designation of the type species for the genus Myotrioza gen. nov. (Psylloidea: Triozidae) - Taylor, Gary S. (Zootaxa, 2016)
Taylor et al. (2016) described twenty new species in one new genus of Australian jumping plant-lice from the plant family Scrophulariaceae but did not nominate a type species, a requirement under the International Code of Zoological Nomenclature under Article 13.3 to make the genus name available (ICZN 1999).